2010
DOI: 10.1021/jf103245z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Process of Making Sweet Wines To Minimize the Content of Ochratoxin A

Abstract: During the drying process of raisins, the grapes are subjected to climatic variations that can result in heavy infections of some fungal species that produce ochratoxin A (OTA), a powerful toxic metabolite, whose maximum permitted content is set by the European Union at 2.0 μg/L for grapes, wine and other drinks derived from the grape. The aim of this paper is to optimize the process of making sweet wines in order to minimize the content of ochratoxin A. The results reflect a reduction of the OTA content in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This has promoted the development of alternative methods of fruits drying under controlled temperature and humidity conditions; such methods produce raisins of a similar quality to those obtained by sun-drying but in less time (Serratosa et al, 2008b). These fruits include cherries, figs, apricots or even raisins (Doymaz, 2006) for the production of sweet wines (Ruiz Bejarano, Rodriguez Dodero, & Barroso, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…This has promoted the development of alternative methods of fruits drying under controlled temperature and humidity conditions; such methods produce raisins of a similar quality to those obtained by sun-drying but in less time (Serratosa et al, 2008b). These fruits include cherries, figs, apricots or even raisins (Doymaz, 2006) for the production of sweet wines (Ruiz Bejarano, Rodriguez Dodero, & Barroso, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…This traditional process is affected by the attack of insects and possible rainfall. This leads to growth of fungi which resulted in loss of high amount of grapes and give rise to the formation of toxins in the wine (Valero et al 2008;Ruíz Bejarano et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative to this traditional sun-drying methodology, that avoids the problems of fungi and insects, has been developed. It is being used for the drying of horticultural products, in general, and grapes, in particular, and consists in forcing the loss of water by means of forced convection with hot air in drying chambers (Vega-Mercado et al 2001;Ruíz Bejarano et al 2010;Serratosa et al 2014). Ruiz et al (2009) found that the musts from chamberdried grapes from Pedro Ximenez exhibited similar volatile profiles than those obtained from sun-dried grapes.…”
Section: Introductionmentioning
confidence: 99%
“…The main raw materials of alcohol beverages are grains and fruits. Hence, brewers consider that mycotoxins pose remarkable risks, but there have been few studies of the fate of mycotoxins in production of alcohol beverages [1][2][3] and, especially as regards distilled beverages, no experimental data have been reported. Meanwhile, in response to increasing consumer demands for food safety, brewers have to present any risks based on experimental data.…”
mentioning
confidence: 99%